MANUAL FOR USING AERIAL PHOTOGRAPHS IN SOIL MAPPING - Mershin,A. P. (1970)
The translation discusses the use of aerial photography in the mapping of soils. Much attention is given to the methods of interpreting soils by aerial photographs and to the study of interpreting soils by their distinctive characteristics in various zones and provinces. Several authors give their views on the interpretation of different soil characteristics such as those of alkali, saline, chestnut, meadow-chestnut, forest-steppe zones, forest and tundra zones, and swamps. The authors also point out that the application of aeromethods in the practice of large-scale soil mapping in the Soviet Union and abroad indicates the use of materials from aerial survey increases considerably the accuracy of soil mapping, reduces the volume of the field work, cuts down its cost and increases the practical value of soil maps. (Author) Trans. of mono. Metodicheskoe Rukovodstvo po Ispolzovaniyu Materialov Aerofotosemki pri Pochvennom Kartirovanii, Moscow, 1964 p1-64.